(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article presents a study related to the analysis of the employed population in the agro-industrial complex, in other words, a qualitative assessment of labor resources in Russian agricultural production was carried out. during the period of economic crises and the negative impact of the pandemic on the production process. The assessment of indicators of the development of the availability of agricultural labor resources was carried out. The study focuses on and evaluates the labor resources that characterize the labor potential of agricultural enterprises. Based on the results of the study, a conclusion is formulated, the essence of which is that in the future it is necessary to continue the transformation of regional human resource management based on artificial intelligence.